2006
DOI: 10.5194/angeo-24-1609-2006
|View full text |Cite
|
Sign up to set email alerts
|

The role of post-sunset vertical drifts at the equator in predicting the onset of VHF scintillations during high and low sunspot activity years

Abstract: Abstract. The day-to-day variability in the occurrence of ionospheric scintillations, which are of serious concern in the trans-ionospheric communications, makes their prediction still a challenging problem. This paper reports on a systematic study in quantitatively identifying the precursors responsible, such as pre-reversal E×B drift velocity, geo-magnetic activity index (Kp) and the Equatorial Ionization Anomaly (EIA) gradient, for the onset of VHF scintillations over a low-latitude station, Waltair (20° N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 29 publications
2
48
0
Order By: Relevance
“…They had used a constant value of L for all the growth rate estimates. The seasonal and solar cycle variability of ESF obtained in the present study agrees with that obtained in previous studies (Subbarao and Krishna Murthy, 1994;Tulasi Ram et al, 2006). The inclusion of L variability also in the growth rate estimates may be able to give better indication of ESF occurrence probability especially while considering on a dayto-day basis.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…They had used a constant value of L for all the growth rate estimates. The seasonal and solar cycle variability of ESF obtained in the present study agrees with that obtained in previous studies (Subbarao and Krishna Murthy, 1994;Tulasi Ram et al, 2006). The inclusion of L variability also in the growth rate estimates may be able to give better indication of ESF occurrence probability especially while considering on a dayto-day basis.…”
Section: Discussionsupporting
confidence: 81%
“…d(h F) is the difference between the maximum layer height in the post sunset period and the layer height at 1800 hr. Here the vertical drift due to recombination effects is neglected as it is not significant in relation to the large vertical drift due to pre-reversal enhancement of the zonal electric field (Tulasi Ram et al, 2006). The L and maximum d(h F)/dt values are estimated for available data on each day, corresponding to the three seasons of solar minimum (1995)(1996) and solar maximum (2002)(2003) years.…”
Section: Experimental Set Up and Data And Methods Of Analysismentioning
confidence: 99%
“…Several workers have studied the plausible causes and effects (Ray et al, 2006; , 2001, 2004Rama Rao et al, 2006;Ram et al, 2006;Nava et al, 2007) of such steep TEC gradients and have strived to develop a predictive mechanism for occurrence for post-sunset scintillations. These exercises have mostly been restricted to the region between the magnetic equator and the northern and southern crests of EIA.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of a developed equatorial ionization anomaly (EIA) in the afternoon hours on the subsequent development of equatorial ionization density irregularities during postsunset hours was suggested by Raghavarao et al (1988) and validated by several workers (Valladares et al, 2001(Valladares et al, , 2004Ray et al, 2006;Rama Rao et al, 2006;Ram et al, 2006;Nava et al, 2007). However the majority of the validation exercise was performed at locations existing between the magnetic equator and the northern and southern crests of the EIA.…”
Section: Introductionmentioning
confidence: 99%
“…Several earlier studies have also shown that a rise in the height of the nighttime F-layer is the most important parameter controlling the generation of spread-F (Farley et al, 1970;Ossakow et al, 1979;Rastogi, 1980;Sastri, 1984;Kelley and Maruyama, 1992;Devasia et al, 2002;Jyoti et al, 2004). Further, Fejer et al (1999), Anderson et al (2004) and Tulasi Ram et al (2006) have shown that, when the post-sunset vertical drifts at the equator are large enough, the necessary condition to trigger the ESF always appears to be present.…”
Section: Introductionmentioning
confidence: 99%